2017
DOI: 10.1002/slct.201700805
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic [3+2] Cycloadditions: Toward Facile Synthesis of Sulfonyl-1,2,3-Triazolyl and Fully Substituted 1,2,3-Triazolyl Glycoconjugates

Abstract: A general strategy was developed for the synthesis of Sulfonyl-1,2,3-triazolyl glycoconjugates (5a-n) and fully decorated 1,2,3triazolyl glycoconjugates (6a-w & 6 aa-6 ah) in the presence of catalytic amounts of organocatalyst. Ramachary-Bressy-Wang organocatalytic azide-ketone [3 + 2]-cycloaddition (OrgAKC) reaction of b-keto sulfones act as internal alkynes with glycosyl azides are reported for the synthesis of Sulfonyl-1,2,3-triazolyl glycoconjugates at 50 8C in good to excellent yields of products in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…38 Ramachary-Bressy-Wang cycloaddition of enolate intermediates and organic azides is the other basic method for one-pot preparation of 1,4-disubstituted-1,2,3-triazoles. [39][40][41][42][43] The reduction of work-up procedures and purication steps, high purity of desired products, short reaction times, high to excellent yields are among the signicant benets of multicomponent one-pot reactions. 44,45 Furthermore, the reaction involving ring opening of epoxides with organic azides in water solvent occurs with perfect regioselectivity and takes advantage of green and benign conditions.…”
Section: Introductionmentioning
confidence: 99%
“…38 Ramachary-Bressy-Wang cycloaddition of enolate intermediates and organic azides is the other basic method for one-pot preparation of 1,4-disubstituted-1,2,3-triazoles. [39][40][41][42][43] The reduction of work-up procedures and purication steps, high purity of desired products, short reaction times, high to excellent yields are among the signicant benets of multicomponent one-pot reactions. 44,45 Furthermore, the reaction involving ring opening of epoxides with organic azides in water solvent occurs with perfect regioselectivity and takes advantage of green and benign conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal and co-workers developed a regioselective, efficient, straightforward, as well as environmentally friendly protocol for the synthesis of sulfonyl-1,2,3-triazolyl glycoconjugates 311 and completely substituted 1,2,3-triazolyl glycoconjugates 312 from glycosyl azides 307 , β-keto sulfone 308 , and substituted phenyl aldehyde 309 using DMSO in an open flask at 50 °C for 1 h and DBU and DMSO for 1 h at RT, respectively (Scheme ). For the DBU-promoted reaction, they found that aprotic polar solvents such as DMSO and DMF gave a good result compared to that with MeOH and CH 3 CN (30% yield).…”
Section: Organocatalytic Synthesis Of 123-triazolementioning
confidence: 99%
“…European Journal of Organic Chemistry cycloaddition between -keto sulfones/substituted phenyl ketone and glycosyl azides for the formation of a diverse substituted 1,2,3-triazolyl glycoconjugates (Scheme 25). [42] Scheme 25. Formation of sulfonyl-1,2,3-triazolyl and 1,2,3-triazolyl glycoconjugates.…”
Section: Eurjocmentioning
confidence: 99%
“…Recently our group have evaluated the straight forward strategy involving organocatalytic enamine‐azide/enolate‐azide cycloaddition between β ‐keto sulfones/substituted phenyl ketone and glycosyl azides for the formation of a diverse substituted 1,2,3‐triazolyl glycoconjugates (Scheme ) …”
Section: General Strategy For the Chemical N‐functionalizationmentioning
confidence: 99%